Cascade Reactions of Unprotected Ketoses with Ketones – A Stereoselective Access to C‐Glycosides. Issue 31 (29th September 2016) - Richter, Celin; Krumrey, Michael; Klaue, Kristin; Mahrwald, Rainer
Abstract : A highly stereoselective de‐Bruyn–Ekenstein rearrangement/aldol condensation/intramolecular oxa‐Michael cascade reaction of unprotected ketoses with ketones was elaborated. By the utilization of this new and operationally simple methodology an access to β‐C‐glycosides is given. Extremely matched and mismatched cases were observed by using with natural or unnatural proline in these cascade reactions. Abstract : Amine‐mediated cascade reactions of unprotected ketoses were elaborated. Extremely matched or mismatched cases were detected by deployment ofd ‐ orl ‐proline in these transformations.